Does use of pooled cohort risk score overestimate the use of statin?: a retrospective cohort study in a primary care setting - Chia, Yook Chin; Lim, Hooi Min; Ching, Siew Mooi (BioMed Central, 2014)
Background: Initiation of statin therapy as primary prevention particularly in those with mildly elevated cardiovascular disease risk factors is still being debated. The 2013 ACC/AHA blood cholesterol guideline recommends initiation of statin by estimating the 10-year atherosclerotic cardiovascular disease (ASCVD) risk using the new pooled cohort risk score. This paper examines the use of the pooled cohort risk score and compares it to actual use of statins in daily clinical practice in a primary care setting. Methods: We examined the use of statins in a randomly selected sample of patients in a primary care clinic. The demographic data and cardiovascular risk parameters were captured from patient records in 1998. The pooled cohort risk score was calculated based on the parameters in 1998. The use of statins in 1998 and 2007, a 10-year interval, was recorded. Results: A total of 847 patients were entered into the analysis. Mean age of the patients was 57.2 ± 8.4 years and 33.1% were male. The use of statins in 1998 was only 10.2% (n = 86) as compared to 67.5% (n = 572) in 2007. For patients with LDL 70-189 mg/dl and estimated 10-year ASCVD risk ≥7.5% (n = 190), 60% (n = 114) of patients were on statin therapy by 2007. There were 124 patients in whom statin therapy was not recommended according to ACC/AHA guideline but were actually receiving statin therapy. Conclusions: An extra 40% of patients need to be treated with statin if the 2013 ACC/AHA blood cholesterol guideline is used. However the absolute number of patients who needed to be treated based on the ACC/AHA guideline is lower than the number of patients actually receiving it in a daily clinical practice. The pooled cohort risk score does not increase the absolute number of patients who are actually treated with statins. However these findings and the use of the pooled cohort risk score need to be validated further.